For byens skyld - konstruktion af Københavns Idrætspark - Mortensen, Morten (Forum for Idræt, 2004)
Politiske, historiske og sociale baggrunde for beslutningen om at anlægge Københavns Idrætspark i 1911. For the city’s sake – the construction of Copenhagen’s Sports Park The creation of Copenhagen’s Sports Park in 1911 can in several ways be seen as the first fragile step on the way to the involvement of voluntary sports in the construction of our welfare state. In the first place the debate and the entire procedure in the city council in Copenhagen demonstrate that sport was regarded as a positive instrument in the prevention of the substantial social and health problems that prevailed in Copenhagen around 1900. In the second place sport – in the form of DIF (The Sports Union of Denmark), Copenhagen’s sporting associations and individuals connected to voluntary sporting activities – was particularly active in this process. In the third place it is interesting that, in constructing the private foundation that was Copenhagen’s Sports Park, Copenhagen Municipal delegated the administration of the city’s sports facilities to the sports associations. This article further describes how Copenhagen’s Sports Park was arranged as an alliance between the city’s conservative politicians and the worker’s movement in the form of the Social Democrat Party.